2010
DOI: 10.1016/j.joca.2009.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage shear dynamics during tibio-femoral articulation: effect of acute joint injury and tribosupplementation on synovial fluid lubrication

Abstract: Objective To determine the effects of acute injury and tribosupplementation by hyaluronan (HA) on synovial fluid (SF) modulation of cartilage shear during tibio-femoral articulation. Methods Human osteochondral blocks from the lateral femoral condyle (LFC) and tibial plateau (LTP) were apposed, compressed 13%, and subjected to sliding under video microscopy. Tests were conducted with equine SF from normal joints (NL-SF), SF from acutely injured joints (AI-SF), and AI-SF to which HA was added (AI-SF+HA). Loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…In large cartilage lesions, the subchondral bone is involved in the degenerative process as well, and focal chondral defects, if left untreated, may even increase in size over time and present with concomitant changes of the underlying subchondral bone plate, either overgrowth or bone loss. 7,8,40 In fact, the functional conditions of articular cartilage and its supporting bone are tightly coupled because injuries of either type adversely affect the entire joint mechanical environment. The biomechanical perturbations caused by osteochondral alterations substantially alter the pattern and magnitude of contact pressure and cartilage strain in the joint.…”
Section: Discussionmentioning
confidence: 99%
“…In large cartilage lesions, the subchondral bone is involved in the degenerative process as well, and focal chondral defects, if left untreated, may even increase in size over time and present with concomitant changes of the underlying subchondral bone plate, either overgrowth or bone loss. 7,8,40 In fact, the functional conditions of articular cartilage and its supporting bone are tightly coupled because injuries of either type adversely affect the entire joint mechanical environment. The biomechanical perturbations caused by osteochondral alterations substantially alter the pattern and magnitude of contact pressure and cartilage strain in the joint.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to native articular cartilage [37, 38], deformation of the hydrogel constructs was highly dependent on their surface friction (Fig. 2F, G).…”
Section: Resultsmentioning
confidence: 78%
“…This may in turn be involved in the initiation of posttraumatic cartilage degeneration by increasing the magnitude of loading-induced tissue strain beyond a physiological level. Nevertheless, although earlier studies suggested an increase in shear strain following superficial cartilage damage and depleted lubrication [3638], surprisingly little is known about the functional relationship between the frictional properties of native or tissue-engineered cartilage and chondrocyte behaviour upon mechanical stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…To accomplish this, three separate compositions were prepared to yield thin hydrogel sheets containing no SSA (alginate methacrylate, or ALMA; Figure We then proceeded to investigate the deformation of these constructs in response to sliding shear motion replicating the mechanical environment of articular cartilage using a custom microscope-mounted loading device and digital image correlation. Similar to native articular cartilage [72,238], deformation of the , and PEG-80S hydrogel constructs were analysed to determine their (A) dynamic coefficients of friction (mean ± SD, n = 5, *** = p ˂ 0.001), (B) compressive moduli at day 1 (mean + SD, n = 3) and (C) mass swelling ratios (bars) as well as water contents (dots) of bilayered constructs (mean ± SD, n = 3). (D) Cross-sections and (E) quantified attenuation values from EPIC-μCT scans illustrating differences in surface hydrogel negative charge densities in bilayered constructs (attenuation scales range from -5,000 (black) to 20,000 (white)).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, although earlier studies suggested an increase in shear strain following superficial cartilage damage and depleted lubrication [72,237,238] % and reacted with a 10-fold molar excess of MAAh over total alginate hydroxyl groups for 24 h on ice and under constant stirring [240]. The pH was regularly adjusted to 8 using 5 M NaOH.…”
Section: Introductionmentioning
confidence: 99%